Confocal Raman Imaging Study Showing Macrophage Mediated Biodegradation of Graphene In Vivo. Issue 11 (2nd April 2013) - Girish, Chundayil Madathil; Sasidharan, Abhilash; Gowd, G. Siddaramana; Nair, Shantikumar; Koyakutty, Manzoor
Abstract This study is focused on the crucial issue of biodegradability of graphene under in vivo conditions. Characteristic Raman signatures of graphene are used to three dimensionally (3D) image its localization in lung, liver, kidney and spleen of mouse and identified gradual development of structural disorder, happening over a period of 3 months, as indicated by the formation of defect‐related D'band, line broadening of D and G bands, increase in ID/IG ratio and overall intensity reduction. Prior to injection, the carboxyl functionalized graphene of lateral size ∼200 nm is well dispersed in aqueous medium, but 24 hours post injection, larger aggregates of size up to 10 μm are detected in various organs. Using Raman cluster imaging method, temporal development of disorder is detected from day 8 onwards, which begins from the edges and grows inwards over a period of 3 months. The biodegradation is found prominent in graphene phagocytosed by tissue‐bound macrophages and the gene expression studies of pro‐inflammatory cytokines indicated the possibility of phagocytic immune response. In addition, in vitro studies conducted on macrophage cell lines also show development of structural disorder in the engulfed graphene, reiterating the role of macrophages in biodegradation. This is the first report providing clear evidence of in vivo biodegradation of graphene and these results may radically change the perspective on potential biomedical applications of graphene.